Previously unknown models of Rheinzabern sigillata-kilns and their relation to the reconstruction of Rheinzabern sigillata-kiln No. 6 - Hissnauer, David; Reutti, Fridolin (Rei Cretariae Romanae Fautorum Acta, 2017)
The “Historisches Museum der Pfalz” in the city of Speyer, Germany, owns five small-scale models of ancient Roman kilns. Being replicas of Roman ‘terra sigillata’-kilns, two of these largely identical models are of exceptional importance.